2012
DOI: 10.5367/te.2012.0113
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Logit and Artificial Neural Networks in Predicting Bankruptcy in the Hospitality Industry

Abstract: Taking financial ratios as independent variables, this study used the framework of a neural network applied to hospitality firm bankruptcy, comparing the results to those of a logit model. Based on the empirical results of the two methodologies, the neural network obtained a higher accuracy rate than the logit model in an in-sample test. However, when tested with a holdout sample for verification, both models achieved a 100% accuracy rate. The study found that 'total liabilities to total assets' was a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 74 publications
(133 reference statements)
1
34
2
1
Order By: Relevance
“…The results of their study showed that the ANN provides a higher accuracy rate for the in-sample test than does the logit model. Park and Hancer (2012) also found that the logit and ANN models both achieved a 100% accuracy rate with a holdout sample.…”
Section: Business Failure Models In Tourism and Hospitality Sectorsmentioning
confidence: 79%
See 1 more Smart Citation
“…The results of their study showed that the ANN provides a higher accuracy rate for the in-sample test than does the logit model. Park and Hancer (2012) also found that the logit and ANN models both achieved a 100% accuracy rate with a holdout sample.…”
Section: Business Failure Models In Tourism and Hospitality Sectorsmentioning
confidence: 79%
“…However, Kim and Gu (2006) recommended the use of a logit model versus the discriminant model because of its theoretical soundness. Park and Hancer (2012) compared the logit model and ANNs for forecasting bankruptcy within the hospitality industry. The results of their study showed that the ANN provides a higher accuracy rate for the in-sample test than does the logit model.…”
Section: Business Failure Models In Tourism and Hospitality Sectorsmentioning
confidence: 99%
“…Results concluded that NN and SVM had an advantage over the others in prediction accuracy, with rates of 92% and 91%, two and three years prior to failure. Park and Hancer (2012) aimed to compare the accuracy of NN to that of a Logit model in predicting bankruptcy in the hospitality industry (hotels, restaurants and entertainment services); so the same sample was used for both analyzed data (40 bankruptcies matched with 40 solvent firms). Results show that NN obtained a higher accuracy rate than Logit in an insample test; and with a hold-out sample, for verification, both models reached a 100% accuracy rate.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of the previous studies related to bankruptcy prediction in the hospitality industry have analyzed one year prior to bankruptcy (Gu & Gao, 2000;Gu, 2002;Kim & Gu, 2006b;Park & Hancer, 2012), and several have analyzed two and three years in advance (Young & Gu, 2010a, Kim & Gu, 2006aLi & Sun, 2012). In this study, three pools of data have been built for the period 2005-2012.…”
Section: Variables Sample and Datamentioning
confidence: 99%
See 1 more Smart Citation